Enhancing Science Learning Outcomes Through Active Learning with Pop-up Book Media in Fifth-Grade Elementary Students - Kudus; Nurrijal (International Journal of Elementary Education, 2024)
The low learning outcomes of students in science subjects pose a problem that requires innovative solutions in the learning process. This study aims to analyze the improvement of fifth-grade elementary students' learning outcomes in the science theme "Human Movement Organs" through the implementation of an active learning model assisted by Pop-up Book media. This research is categorized as Classroom Action Research (CAR) conducted over two cycles. The subjects consisted of 20 students, equally divided into 10 male and 10 female students. Data collection techniques included tests, interviews, observations, and documentation. Data were analyzed qualitatively and quantitatively using descriptive methods. The findings reveal that in the first cycle, 60% of students achieved mastery, while in the second cycle, this percentage increased to 85%. The integration of active learning approaches with Pop-up Book media proved effective in facilitating students' understanding of complex science concepts. The study concludes that the use of Pop-up Book media not only makes learning more engaging and interactive but also significantly improves student learning outcomes and enhances the overall quality of classroom instruction.